A single sub-anaesthetic dose of propofol to reduce patient recall of peribulbar block. Issue 3 (1st October 2000) - Hocking, G; Balmer, H G R
Abstract : We audited a total of 1233 patients scheduled for elective cataract extraction or trabeculectomy using peri-bulbar anaesthesia. A bolus of propofol provided sedation to cover insertion of the block. During an initial two-year period we collected data on the amount of propofol used to sedate 481 patients. Multiple linear regression analysis was then used to obtain an equation to link the dose used to age and weight in those who were adequately sedated. The dose of propofol in milligrams was calculated as 56 + 0.25 x weight (kg) - 0.53 x age (yrs). We subsequently assessed the effectiveness of this formula at abolishing recall of the injections whilst not compromising the airway on a further 752 patients. This simple regime was effective at abolishing recall of the block in 78.6% of the patients studied and avoids the cost and logistic implications of more complicated drug delivery systems. Use of the formula does not significantly alter the incidence of recall compared to sedation provided by an experienced ophthalmic anaesthetist. We hope it will provide a guide for more junior anaesthetists to obtain the satisfactory sedation level that comes with experience.